Analisis Model UTAUT pada Adopsi TIK di Institusi Komisi Pemilihan Umum (KPU) - Sanofi, Zuhairi; Sherlin, Intan (Jurnal Pekommas, 2023)
The Covid-19 pandemic has had an impact on the management of government agencies. To maintain optimal employee performance, efforts have been made to adopt Information and Communication Technology (ICT). One way is to use the Zoom Meeting application as an alternative media for organizational communication within the General Elections Commission (KPU). However, the quality of this application-based implementation needs to be evaluated to identify its strengths and weaknesses so that its use can be relevant to organizational goals. This evaluation uses the Unified Theory of Acceptance and Use of Technology (UTAUT) model combined with the time zone construct. This study uses a quantitative method involving 254 respondents taken through a voluntary response convenience technique from internal KPU institutions (covering 34 provinces). The results show that of the five UTAUT constructs, performance expectancy and facilitation conditions positively affect employee behavioral intentions using the Zoom Meeting application during the Covid-19 pandemic. In comparison, the other three constructs have the opposite effect.